PENGARUH TINGKAT DISIPLIN KERJA, MOTIVASI KERJA DAN KOMITMEN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM KABUPATEN MERAUKE - Leonarti Leonarti; Muhammad Idrus Taba; Andi Reni (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2019)
This study aims to determine the effect of the level of work discipline, work motivation and work commitment to the performance of employees at the Public Works Department of Merauke Regency.This research uses quantitative research, quantitative research is a process of finding knowledge using numerical data as a tool to analyze information about what want to know.The results of this study found that work discipline, work motivation and work environment simultaneously have a positive and significant effect on employee performance, work discipline has a positive and significant impact on employee performance, high work motivation can be proven to contribute positively and significantly to improving employee performance , the commitment of good organization proved to give positive and significant contribution to the improvement of employee performance at the Office of Public Works Department of Merauke Regency.